2012
DOI: 10.1200/jco.2011.40.8906
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood in Survivors of Hodgkin Lymphoma: An EORTC-GELA General Population Case-Control Study

Abstract: Survivors of HL had slightly but significantly fewer children after treatment than matched general population controls. The difference concerned only survivors who had children before treatment and appears to have more personal than biologic reasons. The chance of successful post-treatment parenthood was 76%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
1
26
1
Order By: Relevance
“…Unexpectedly, the desire for a child could only be fulfilled by 30% of the patients. Compared to previous studies [18,32,33], the rate found in our study is low. This is likely to be related to the fact that 40% of our patients underwent allogeneic stem cell transplantation, which is known to cause lasting sterility in a high proportion of patients [34][35][36].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, the desire for a child could only be fulfilled by 30% of the patients. Compared to previous studies [18,32,33], the rate found in our study is low. This is likely to be related to the fact that 40% of our patients underwent allogeneic stem cell transplantation, which is known to cause lasting sterility in a high proportion of patients [34][35][36].…”
Section: Discussioncontrasting
confidence: 99%
“…While, at the time of diagnosis, patients that already had a child expressed a stronger desire for further parenthood than patients without a child, the opposite was true after the end of treatment [19]. In Hodgkin's lymphoma, patients that already had a child at the time of diagnosis had lower post-treatment birth rates than patients without a child [32].…”
Section: Discussionmentioning
confidence: 99%
“…Data on effect estimates (HR, RR, RaR, and OR) of pregnancy and live birth were extracted from the remaining 18 articles, all of which were published in peer-reviewed journals between 2004 and 2018 (Byrne et al, 2004;Hodgson et al, 2007;Syse et al, 2007;Madanat et al, 2008;Cvancarova et al, 2009;Reulen et al, 2009;Pivetta et al, 2011;Stensheim et al, 2011;van der Kaaij et al, 2012;Baxter et al, 2013;Dillon et al, 2013;Hartman et al, 2013;Brämswig et al, 2015;Chow et al, 2016;Armuand et al, 2017;Anderson et al, 2018a;2018b;Thouvenin-Doulet et al, 2018). Details of the characteristics of the included studies are presented in TABLE 1.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the participants represented 50.4% of the target population, which is lower than the proportions observed in surveys of the Dutch or Nordic general populations 17,18 but similar to that reported in the European Organization for Research and Treatment of Cancer survey of Hodgkin lymphoma survivors. 8 Third, the collected health data had no medical confirmation, and a memory bias cannot be excluded. Although targeted inquiries were used on the form, the possible bias probably concerns only health disorders that did not require permanent medication or that had no major impact on personal daily life.…”
Section: Discussionmentioning
confidence: 99%
“…The nonvalidated Life Situation Questionnaire (LSQ) addresses issues not available in other validated questionnaires, including the following sections: sociodemographic data, including marital status and highest level of education 6 ; parenthood data; education, work, and insurance; health situation, including height, weight, and detailed information on immediate post-treatment fatigue (within 3 years), post-treatment health disorders, and current treatments; and social situation. 7,8 The LSQ used targeted inquires to collect information. The weight (kg)-to-height (m) 2 ratio was used to calculate the body mass index (BMI) at the time of survivorship assessment; obesity was defined as a BMI ≥30 kg/m 2 .…”
Section: Questionnairesmentioning
confidence: 99%